Comparative Study of Intelligent and Smart Development Platforms Employed for Internet of Thing’s Applications - et. al., Ranvir A. Ghate, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Internet of Things (IoT) describes the network of advanced microcontroller based embedded system having capability of connecting and exchanging data with other electronics devices and systems over the internet. The IoT applications are enabling the integration of internet or cyber world with the physical world. It provides the facility of interaction between human beings and computers with the millions of things, which are embedded system and other internet connected objects. The System on Chip (SoC) based processor development platforms are becoming extensively popular in development of different embedded systems and hence, IoT networks because of their low cost, ultra-low power, small size and ease in deployment. In this paper we investigated the many development platforms, such as Arduino Uno, Raspberry Pi, Beaglebone Black, Adafruit feather, etc., are made available by the vendors which is revolutionizing the IoT based embedded systems. This paper depicts review and survey of development platforms and different technologies for the development of the sophisticated and smart systems for numerous IoT applications. Therefore, extensive literatures survey has been carried out and studied, and provided a comparative solution to choose a relevant IoT development platform for various applications.